Aplikasi Modified Atmosphere Packaging (MAP) Berbasis Nitrogen terhadap Mutu Fisik Cabai Merah (Capsicum annuum L.) selama Penyimpanan - Mutiar, Sri; Arziyah, Dewi; Kasim, Anwar; Rehulina, Rehulina (Sekolah Tinggi Pertanian Kutai Timur, 2025)
Physical and physiological red chili (Capsicum annuum L.) deterioration after harvest often leads to a decline in quality and contributes to price fluctuations in the domestic market. Therefore, effective packaging technology is required to extend shelf life and maintain the quality of red chili. One promising approach is Modified Atmosphere Packaging (MAP) using nitrogen. Nitrogen gas is inert, odorless, tasteless, and can replace oxygen to suppress respiration, oxidation, and color degradation. This study aimed to evaluate the effect of nitrogen packaging on weight loss, moisture content, and color attributes of red chili during storage at room temperature. The experiment was arranged in a completely randomized design (CRD) with two factors, namely packaging treatment (without nitrogen and with nitrogen) and storage duration (0, 3, 6, 9, and 12 days), each with three replications. The observed parameters included weight loss, moisture content, and color (L, a, b values). The results revealed that red chili packaged with nitrogen exhibited a slower increase in weight loss compared to the control, reaching only 3.62% on day 12, lower than 4.29% without nitrogen. Moisture content in nitrogen-packaged chili was relatively more stable during storage, although some fluctuations occurred. Furthermore, color analysis showed that nitrogen packaging better preserved brightness (L) and redness (a), resulting in fresher appearance. Nitrogen based packaging effectively maintained the physical quality of red chili during storage, highlighting its potential to reduce postharvest losses and enhance the competitiveness of horticultural products.